Model Kebijakan Mixed Scanning Dalam Implementasi Kebijakan Pengembangan Pariwisata di Provinsi Banten yang Berkelanjutan - Reviana, Maghfira Nur; Jumiati, Ipah Ema; Salsabilla, Diviani; Prasetio, Ardi (Jurnal Administrasi Karya Dharma, 2025)
This study analyzes the implementation of tourism development policies in Banten Lama, Banten Province, using a mixed scanning model. Banten Lama, as a cultural heritage area, has great potential for historical and religious tourism. This research aims to evaluate the effectiveness of policy implementation and identify challenges faced. The research method used is descriptive analysis with primary data obtained through interviews and secondary data from documents and archives. The results show that although the strategic policy has been well formulated through the 2017 MoU and Serang City Regional Regulation No. 14/2014, its implementation in the field is more incremental and adaptive to various obstacles, such as inter-agency coordination, conflicts of interest, and human resource capacity. The mixed scanning model proved relevant in analyzing this complexity, allowing for strategy adjustments while sticking to long-term goals. The research recommends the establishment of a special management agency for Banten Lama, the preparation of standardized SOPs, empowerment of localcommunities, and strict enforcement of rules to realize sustainable tourism governance and optimization of Banten Lama's potential as a leading destination.